Child Maltreatment and Medical Traumatic Stress—A Double-Edged Sword - Rony Kapel Lev-ari; Roy Aloni; Amit Shalev; Avi Elbaz; Yael L. E. Ankri; Shiri Ben-David; Naomi Kahana Levy; Fortu Benarroch; Amichai Ben-Ari (Children)
Background/Objectives: Medical procedures can be a traumatic event for both children and their parents. Children who have experienced maltreatment or early traumatic experiences are at a higher risk for various emotional, behavioral, and health issues, including declining mental health. This may include experiencing heightened distress following medical procedures. The goal of this paper is to investigate the risk of distress symptoms following medical procedures for children with a history of child maltreatment vs. controls. Methods: A prospective study of 219 parents and children hospitalized in a pediatric surgical ward was conducted, with participants divided into study and control groups based on their reports of early traumatic experiences. Questionnaires measuring psychological distress were administered before the medical procedure and 3–5 months after discharge. Results: Children from the study group displayed significantly more distress symptoms before and after the procedure, with a substantial post-procedure increase. Parents of children who endured prior trauma and child maltreatment also exhibited elevated pre-procedure distress. Prior trauma and child maltreatment independently contributed to heightened medical distress. Post-procedure child distress was influenced by the early traumatic events and also by family support, socioeconomic status, and parental procedure-related post-traumatic stress symptoms. Conclusions: Children with a history of child maltreatment and trauma show an increased chance of psychological distress following medical procedures. Medical teams should be aware of this heightened risk and provide appropriate support.